Analyzing the Policy, Regulatory and Institutional Framework for Implementation of Redd-plus in India - Kohli, Priyanka; Sharma, J. V. (Indian Forester, 2014)
Forests are a vital national resource, with global concern, having local importance related to livelihood of people living in and around the forests. Conservation of forests is a traditional practice among the people, depending on forest for their sustenance and livelihood needs. In this context, the paper reviews the policy, regulatory and institutional framework of forest governance in India. The gaps in the policy, regulatory and institutional framework are identified. The paper suggests directions for policy interventions to overcome the gaps identified. Institutional arrangement for implementation of REDD-plus under the forest governance framework is described in the paper. Recommendations include safeguards to be adopted under REDD-plus and possible forest governance models. Decentralization of forest rights and community based forest governance is identified as critical to the success of REDD-plus. Community based forest governance is a form of participatory and inclusive management and a key factor for implementation of REDDplus in India.